Lebih dari Sekedar Kumpul: Pembinaan Kristiani dalam Persekutuan Mengukir Identitas Pemuda - Alfons Renaldo Tampenawas; Semuel Selanno (Sekolah Tinggi Teologi Parakletos Tomohon, 2025)
Abstract: This research aims to analyze the urgency of restructuring Church Youth Fellowships in response to the identity crisis faced by Christian adolescents (aged 15–30), which is exacerbated by the digital era. The method employed is a Descriptive Qualitative Literature Review, synthesizing existing theoretical concepts and findings. The results indicate that the ineffectiveness of fellowships stems from functional failure, often reducing them to mere social activities. The derived solution and main finding are the necessity of transforming into an integrated discipleship community centered on two pillars: 1) Implementing Holistic Nurturing utilizing digital technology as a discipleship tool while building an authentic self-concept rooted in Christ; and 2) Establishing a consistent Multilevel Collaboration among the church, family, and community. The practical implication of this study is to offer an ecological framework for the church to develop youth spiritual resilience. This transforms the fellowship from a vulnerable vessel into a solid foundation for character, ensuring the consistency of Christian values across all digital and physical domains of life. Abstrak: Penelitian ini bertujuan menganalisis urgensi restrukturisasi Persekutuan Pemuda Gereja dalam menghadapi krisis identitas remaja Kristen (15–30 tahun) yang diperburuk oleh era digital. Metode yang digunakan adalah Studi Literatur Kualitatif Deskriptif melalui sintesis temuan dan konsep teoretis. Hasil kajian menunjukkan bahwa inefektivitas persekutuan disebabkan kegagalan fungsi, di mana ia hanya menjadi aktivitas sosial semata (